The Loop Diuretic Bumetanide Blocks Posttraumatic p75(NTR) Upregulation and Rescues Injured Neurons - Shulga, Anastasia (J Neurosci, 2012)
Injured neurons become dependent on trophic factors for survival. However, application of trophic factors to the site of injury is technically extremely challenging. Novel approaches are needed to circumvent this problem. Here, we unravel the mechanism of the emergence of dependency of injured neurons on brain-derived neurotrophic factor (BDNF) for survival. Based on this mechanism, we propose the use of the diuretic bumetanide to prevent the requirement for BDNF and consequent neuronal death in the injured areas. Responses to the neurotransmitter GABA change from hyperpolarizing in intact neurons to depolarizing in injured neurons. We show in vivo in rats and ex vivo in mouse organotypic slice cultures that posttraumatic GABA(A)-mediated depolarization is a cause for the well known phenomenon of pathological upregulation of pan-neurotrophin receptor p75(NTR). The increase in intracellular Ca(2+) triggered by GABA-mediated depolarization activates ROCK (Rho kinase), which in turn leads to the upregulation of p75(NTR). We further show that high levels of p75(NTR) and its interaction with sortilin and proNGF set the dependency on BDNF for survival. Thus, application of bumetanide prevents p75(NTR) upregulation and neuronal death in the injured areas with reduced levels of endogenous BDNF.